ANALISIS LIKUIDITAS, SOLVABILITAS, DAN PROFITABILITAS TERHADAP PERTUMBUHAN LABA PADA PERUSAHAN DI BURSA EFEK INDONESIA - Ananda, Emiya Putri; Tipa, Handra (LPPM Universitas Putera Batam, 2022)
The purpose of this study was to determine the effect of liquidity, solvency, and profitability on profit growth in automotive companies listed on the Indonesia Stock Exchange. The financial ratios used in the study included Current Ratio (CR), Debt to Equity Ratio (DER), and Net Profit Margin (NPM). The sampling method in this study using purposive sampling contained from 13 automotive companies listed on the Indonesia Stock Exchange only 8 were used as samples. The data analysis method uses multiple linear regression analysis. The results of the tests in this study partially showed that the current ratio had no significant effect on profit growth, the debt to equity ratio had a significant effect on profit growth, and net profit margin had no significant effect on profit growth. Simultaneously current ratio, debt to equity ratio, and net profit margin have a significant effect on profit growth.